Expanded child support grant eligibility and later-life mortality among mothers in rural South Africa - Rishika Chakraborty; Erika T. Beidelman; Maria Klein; Lindsay C. Kobayashi; Katherine Eyal; Chodziwadziwa Whiteson Kabudula; Molly Rosenberg (Global Public Health)
The South African Child Support Grant (CSG) may be associated with mother’s mortality via pathways linked to CSG spending, however, this relationship remains uncertain. To identify the association between CSG eligibility and mortality among mothers, we exploited exogenous variation in CSG-eligibility due to iterative age-eligibility expansions. Data were obtained from the Agincourt Health and Socio-Demographic Surveillance System. Mothers contributed person-time from age 50 till they died or were censored in March 2022. The cumulative duration of CSG-eligibility was calculated using children’s birthdates and CSG expansion years and dichotomised at the median to give high (>18) and low (≤18) duration. We matched mothers with high vs low duration of CSG-eligibility based on their birth years and number of children. To estimate the association between cumulative duration of CSG eligibility by age 50 and subsequent all-cause mortality, we specified Cox proportional hazards models, adjusting for sociodemographic variables. Duration of CSG-eligibility was not associated with mortality among mothers in the full sample (adjusted HR: 1.05, 95% CI: 0.75, 1.44) nor within sociodemographic sub-groups. Future studies should explore the association of CSG eligibility with premature and cause-specific mortality in mothers and at different life course timings to promote their health and longevity.